Self-Confidence as a Mediator Between Entrepreneurship Education and Entrepreneurial Intention - Danan Wuryanto Pramono; Ernani Hadiyati; Rosidi Rosidi; Gunadi Gunadi (Mandalika Institute, 2026)
Entrepreneurship education has been widely recognized as a strategic instrument for fostering entrepreneurial intention among students. However, the mechanism through which entrepreneurship education influences entrepreneurial intention, particularly through psychological factors, remains underexplored and shows inconsistent findings in prior studies. This study aims to examine the role of self-confidence as a mediating factor between entrepreneurship education and entrepreneurial intention, highlighting its conceptual novelty as a psychological pathway. Using a qualitative approach with a systematic literature review method, this research analyzes and synthesizes peer-reviewed international journal articles selected based on relevance, credibility, and conceptual alignment. The analysis applies a structured content analysis technique to identify patterns, relationships, and theoretical explanations regarding the mediating role of self-confidence. The findings indicate that entrepreneurship education not only directly influences entrepreneurial intention but also indirectly strengthens it through the development of self-confidence. Specifically, experiential learning, exposure to role models, and practical simulations enhance students’ confidence, which in turn increases their perceived capability to engage in entrepreneurial activities. This demonstrates that self-confidence functions as a critical psychological mediator that translates educational experiences into entrepreneurial motivation. This study provides an analytical contribution by clarifying the mediating mechanism linking entrepreneurship education and entrepreneurial intention. The findings emphasize the importance of integrating confidence-building pedagogical strategies into entrepreneurship curricula to enhance students’ readiness for entrepreneurial careers and support sustainable economic development.